Augmenting metallobasicity to modulate gold hydrogen bonding. Issue 69 (9th August 2022) - Maltz, Logan T.; Wilkins, Lewis C.; Gabbaï, François P.
Abstract : Enhancing gold's metallobasicity through chloride to phenyl ligand substitution afforded an observable increase in the strength of the Au(i )⋯H–O hydrogen bond. Abstract : We report the synthesis and characterization of two phosphine gold carbinol species designed to support intramolecular Au⋯H–O hydrogen bonding. Increasing the metallobasicity of gold through chloride to phenyl ligand substitution produced an observable increase in this hydrogen bond's strength which was analyzed experimentally and computationally.